Implantation assays using the integument of early stage Bombyx larvae: Insights into the mechanisms underlying the acquisition of competence for metamorphosis. (July 2017) - Inui, Tomohiro; Daimon, Takaaki
Graphical abstract: Highlights: Piepho's classic experiments from the 1930s were revisited using knockout Bombyx . The epidermis of neonate larvae can directly metamorphose to produce pupal cuticle. Juvenile hormones prevent pupal commitment of the epidermis of neonate larvae. Unidentified blood-borne factor(s) may confer competence for metamorphosis. Abstract: It is widely accepted that the anti-metamorphic action of insect juvenile hormones (JHs) is required to inhibit larval-pupal metamorphosis. However, recent studies using RNAi or knockout techniques reveal that larval status may be maintained independently of JHs during the early larval stages. To investigate why larvae of very early instars do not have competence to metamorphose and how they acquire this competence through larval development, we revisited the classic experiments of Piepho (ca. 1930s) and performed implantation assays using the integument of very young larvae of the silkworm, Bombyx mori . Here, we demonstrate that when the integuments of neonate larvae or newly molted second instar larvae are implanted into last instar host larvae, they are able to directly produce pupal cuticle at the time of pupal metamorphosis of the host. To investigate whether the pupal commitment of implants from the neonate first instar larvae is repressed by JHs, the integuments of Met1 knockout larvae lacking a functional JH receptor were implanted into penultimate instar larvae. We found that the implants of Met1 knockout neonate larvae produced patched pupal cuticles after the host larval molt, whereas those of the wild-type strain produced only larval cuticle without any trace of pupal cuticle. Taken together, our results suggest that the epidermis of very early instar larvae can be pupally committed when provided with unidentified blood-borne factor(s) present in final-instar larvae, and that JHs can block the action of that factor(s) to prolong the feeding period until larvae attain a size appropriate for metamorphosis.